Education in Persia during the Second half of the Nineteenth century - AbdulRazaq, Shaheen Suham (Al-Adab Journal, 2022)
This study was falled within the perspective of the evolution of classical education in Iran, and prospects for research, and associated with the issue of composition and evolution of the educational structure of Iran. The objectives of this study were to draw attention to the fundamental component of the educational field and for a few extra factions within the institution in Iran. The hypothesis that stands by this study was that we cannot understand this field and the positions and roles of potential and ongoing conflicts and the challenges (including forms that Itemizer by all the actors) without a correct diagnosis of the status of Koranic schools within the field of education. In addition, some of the important stakes in this field, and more broadly those associated with the issue of culture in Iran, cannot be understood if we do not try to know this kind of education. Then the study was focused on two main points: 1 - formative frameworks of the education system in the ancient Iranian state, as we shall show how it came about this system. 2 - regulatory frameworks, and educational for the education system of old, and rather programmed to carry them through their formative education.